Investigation of urine metabolome of BALB/c mouse infected with an avirulent strain of Toxoplasma gondii - Zhou, Chun-Xue; Li, Ling-Yu; Huang, Cui-Qin; Guo, Xu-Dong; An, Xu-Dian; Luo, Fang-Fang; Cong, Wei (Parasites & vectors, 2022)
The protozoan parasite Toxoplasma gondii is a major concern for human and animal health. Although the metabolic understanding of toxoplasmosis has increased in recent years, the analysis of metabolic alterations through noninvasive methodologies in biofluids remains limited. Here, we applied liquid chromatography-tandem mass spectrometry (LC-MS/MS)-based metabolomics and multivariate statistical analysis to analyze BALB/c mouse urine collected from acutely infected, chronically infected and control subjects. In total, we identified 2065 and 1409 metabolites in the positive electrospray ionization (ESI +) mode and ESI - mode, respectively. Metabolomic patterns generated from principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) score plots clearly separated T. gondii-infected from uninfected urine samples. Metabolites with altered levels in urine from T. gondii-infected mice revealed changes in pathways related to amino acid metabolism, fatty acid metabolism, and nicotinate and nicotinamide metabolism. This is the first study to our knowledge on urine metabolic profiling of BALB/c mouse with T. gondii infection. The urine metabolome of infected mouse is distinctive and has value in the understanding of Toxoplasmosis pathogenesis and improvement of treatment.